Pricing, reimbursement and market access issues in the United States and Europe - Blansett, Lee; Colasante, Walter (Henry Stewart Talks, 2009)
Different structures and philosophies: EU and US, Fragmented health funding, US expenditure, Private payers shift costs, Cost sharing, Generics, Risk of federal negotiations, Biomarkers, Is value based pricing clear?, Pricing, reimbursement and market access issues in Europe, Current and future reimbursement mechanisms, Why EU states intervene, the dynamics of price versus reimbursement, Effective way of reducing the cost of healthcare, Launching new products, EU countries and mechanisms of controlling their budget, Pharmaeconomics, Cost utility analysis and quality adjusted life year, Politics, ethics and future reimbursement systems